Preserving Metamagnetism in Self-Assembled FeRh Nanomagnets - Motyčková, Lucie; Arregi, Jon Ander; Staňo, Michal; Průša, Stanislav; Částková, Klára; Uhlíř, Vojtěch (ACS applied materials & interfaces, 2023)
Preparing and exploiting phase-change materials in the nanoscale form is an ongoing challenge for advanced material research. A common lasting obstacle is preserving the desired functionality present in the bulk form. Here, we present self-assembly routes of metamagnetic FeRh nanoislands with tunable sizes and shapes. While the phase transition between antiferromagnetic and ferromagnetic orders is largely suppressed in nanoislands formed on oxide substrates via thermodynamic nucleation, we find that nanomagnet arrays formed through solid-state dewetting keep their metamagnetic character. This behavior is strongly dependent on the resulting crystal faceting of the nanoislands, which is characteristic of each assembly route. Comparing the calculated surface energies for each magnetic phase of the nanoislands reveals that metamagnetism can be suppressed or allowed by specific geometrical configurations of the facets. Furthermore, we find that spatial confinement leads to very pronounced supercooling and the absence of phase separation in the nanoislands. Finally, the supported nanomagnets are chemically etched away from the substrates to inspect the phase transition properties of self-standing nanoparticles. We demonstrate that solid-state dewetting is a feasible and scalable way to obtain supported and free-standing FeRh nanomagnets with preserved metamagnetism.
Keywords: antiferromagnetism; self-assembly; supercooling; metamagnetism; solid-state dewetting; FeRh